Online tools supporting the conduct and reporting of systematic reviews and systematic maps: a case study on CADIMA and review of existing tools - Kohl, Christian; McIntosh, Emma J.; Unger, Stefan; Haddaway, Neal R.; Kecke, Steffen; Schiemann, Joachim; Wilhelm, Ralf (Environmental Evidence, 2018)
Systematic reviews and systematic maps represent powerful tools to identify, collect, evaluate and summarise primary research pertinent to a specific research question or topic in a highly standardised and reproducible manner. Even though they are seen as the “gold standard” when synthesising primary research, systematic reviews and maps are typically resource-intensive and complex activities. Thus, managing the conduct and reporting of such reviews can become a time consuming and challenging task. This paper introduces the open access online tool CADIMA, which was developed through a collaboration between the Julius Kühn-Institut and the Collaboration for Environmental Evidence, in order to increase the efficiency of the evidence synthesis process and facilitate reporting of all activities to maximise methodological rigour. Furthermore, we analyse how CADIMA compares with other available tools by providing a comprehensive summary of existing software designed for the purposes of systematic review management. We show that CADIMA is the only available open access tool that is designed to: (1) assist throughout the systematic review/map process; (2) be suited to reviews broader than medical sciences; (3) allow for offline data extraction; and, (4) support working as a review team.
Keywords: Evidence synthesis; Managing systems; Rapid review; Review management; Systematic review software; Text mining; Time management; _Added-ailr-2024

Classroom dialogue and digital technologies: A scoping review - Major, L.; Warwick, P.; Rasmussen, I.; Ludvigsen, S.; Cook, V. (Education and Information Technologies, 2018)
This article presents a systematic scoping review of the literature focusing on interactions between classroom dialogue and digital technology. The first review of its type in this area, it both maps extant research and, through a process of thematic synthesis, investigates the role of technology in supporting classroom dialogue. In total, 72 studies (published 2000–2016) are analysed to establish the characteristics of existing evidence and to identify themes. The central intention is to enable researchers and others to access an extensive base of studies, thematically analysed, when developing insights and interpretations in a rapidly changing field of study. The discussion illustrates the interconnectedness of key themes, placing the studies in a methodological and theoretical context and examining challenges for the future.
Keywords: Classroom dialogue; Collaboration; Digital technology; Edtech; Talk; _THEME: Teacher Professional Development

An Overview of ICT for Education of Refugees and IDPs - Joynes, Chris; James, Zoe (K4D, Knowledge, Evidence, and Learning for Development, 2018)
This rapid review examined examples of ICT approaches to address the education needs of those living in IDP and refugee camps and lessons learned from these experiences. Although ICT is considered a good system to fulfil the education needs within refugee settings, many studies conclude that access to ICTs in schools or at home is not sufficient to improve learning outcomes. It is due to the role of a mentor or tutor figure is seen as key to productive learner engagement with technology, and the effectiveness of ICT-based education is reliant on appropriate teacher training to ensure successful up-take at the classroom level (Tauson & Stannard 2018: 47, 62; UNESCO 2018: 74; Carlson 2013: 30). Secondly, in terms of content, ICTs for education should provide content that is responsive or adaptable to the learners’ level, is implemented in line with the local curriculum and also is relevant to the learners’ context (Tauson & Stannard 2018: 36-38, 61). Despite this potential for ICTs, there remains a broad lack of evidence related to education in refugee settings (Burde et al. 2015; Tauson & Stannard 2018; World Bank 2016). In particular, more information is needed on pedagogic design, on the effective use of ICTs for learning, on the role of ICTs in ensuring continuity of and linkages between learning in formal and non-formal settings, on the role of ICTs in educational data-gathering, and on the cost-effectiveness of ICT-led interventions (Burde et al 2015; Tausin & Stannard 2018; Carlson 2013). In light of the availability of evidence, some of the studies cited here instead supplement their findings by drawing on observational studies, and on studies on effective ICT usage from learners in non-refugee contexts (Burde et al. 2015; Tauson & Stannard 2018).
Keywords: Google Scholar/ "education technology" refugees; RER theme_general; RER theme_pedagogies and modalities; ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode